WACANA PENGAWASAN KOMISI PENYIARAN INDONESIA PADA KONTEN MEDIA DIGITAL - Mawar Meini Surentu, (2020)
Starting from the Indonesian Broadcasting Commission who wants to immediately oversee the contents of content on digital media. This study discusses the reasons for the Indonesian Broadcasting Commission who wants to be included in the supervision of the contents of content on digital media. This study aims to describe the reasons of the Indonesian Broadcasting Commission's surveillance discourse on digital media content, and find out how the community's response is related to the discourse carried out by the Indonesian Broadcasting Commission. The research theory used is Media Hegemony Theory. The research approach used in this study is a qualitative approach to the case study method. Data collection techniques used in this study were observation and interviews. Observations were made by collecting videos containing statements from the Indonesian Broadcasting Commission and the Ministry of Communication and Information. Interviews were conducted on a number of digital media users to find out public opinion regarding this discourse. The results of the research obtained through video observations that have been made show that the Indonesian Broadcasting Commission has a new strategic step to participate in overseeing the contents of content on digital media. In addition, the Indonesian Broadcasting Commission also received encouragement from broadcasting institutions in Indonesia, what is desirable is not only supervision of television and radio, but also surveillance is carried out on digital media which is far more freely accessed anytime and anywhere. The supervision of the Indonesian Broadcasting Commission on digital media content to be carried out is not yet clear how the arrangement is, the reason is because the regulation is still in the discussion stage. According to interviews with several digital media users, there are pros and cons in the community. People who approve this supervision are of the opinion that the need for more supervision of digital media, while people who do not approve of this supervision because the Indonesian Broadcasting Commission will limit the creativity of content creators in digital media, as well as the security arrangements available in digital media are sufficient for media users as a form of surveillance. At present supervision of digital media is still a responsibility of the Ministry of Communication and Information. Therefore, the Indonesian Broadcasting Commission is not yet required to oversee the contents of content on digital media.